DEVELOPMENT OF UZBEKISTAN: MODERNIZATION OF AGRICULTURE AND EXCHANGE INNOVATIONS IN THE TEXTILE INDUSTRY (American Journal of Technology and Applied Sciences, 2024)
This article describes significant initiatives launched by the Uzbekistan government for the development of agriculture and the textile industry. Through collaboration between the Ministry of Agriculture, the Ministry of Economy and Finance, and the Cotton-Textile Cluster Association, steps have been taken to implement international financial reporting standards. Plans for conducting independent audits of the clusters' performance are also discussed. Special attention is given to the role of the Uzbek Republican Commodity and Raw Materials Exchange and new exchange instruments, such as cotton futures contracts, in the development of agriculture and the attraction of foreign investors. It is emphasized that these measures contribute to economic growth, improvement of the population's well-being, and the resolution of social issues.